Social Support And Psychological Well-Being Among Omsc Cte Students During The Pandemic - Pastrana, Nimfa (International Journal of Educational Research & Social Sciences, 2022)
This study was conducted to find out the effect of physical activity to the psychological well-being in terms of self-esteem and self-efficacy of persons with disability. 40 students from CORD Foundation in San Jose, Occidental Mindoro were the respondents of the study. The intervention program was carried out for eight (8) consecutive Saturdays. This consisted of aerobic exercises and structured games. The effectiveness of the intervention program was determined using the One-Group Pre-test (degree of selfesteem and self-efficacy of the respondents before the intervention program and Post-test (degree of self-esteem and self-efficacy of the respondents after the intervention program) Design. Data were analysed using the t-test for dependent means. The statistical calculations showed that the difference on the self-esteem and self-efficacy were significant thus, it can be concluded that physical activity is effective in enhancing the self-esteem and self-efficacy of the PWDs. Thus it is recommended that physical activity be sustained to people with disabilities.